ANALYSIS OF TEACHERS’ COMPETENCE IN THE ACCELERATED PROGRAMS IN JUNIOR HIGH SCHOOLS - Ni?matuzahroh, Ni?matuzahroh (COUNS-EDU: The International Journal of Counseling and Education)
The purpose of this research is to discover an enhanced model of teaching capability in acceleration program in junior high schools in Malang. Subjects were chosen with purposive sampling from the teachers and students in accelerated program in SMP 1 and SMP 3 Malang. The data were collected using the methods of observation, interviews, FGD, and documentation. The analysis  was descriptive qualitative in nature. The result showed that the teachers were aware that students in the accelerated program had characteristics distinguishing themselves from others. The learning process in an accelerated class was not different from the regular class because the teachers in such a regular class applied a monotone teaching method, such lecturing and tasks oriented teaching. This research revealed that most teachers viewed that  students, who possess high cognitive capability, were able to understand the materials taught on their own by giving numerous practical  questions.  There were also only  few teachers oriented to constructing an interesting learning atmosphere alongside authentic assessment. Concerning facilities and infrastructures, teachers and students stated that the two are considered adequate as shown by the availability of classrooms, learning media such as LCD and laptop, internet, other materials. However, teachers admitted that they had a main hindrance:  limited capability in applying learning methods using IT or technology,  for example, the LCDs, laptops, and the like. The teachers find it difficult to make  combined materials from multiple grade levels. Limited time allotment and concentrated materials caused the teachers to feel that their teaching hadn?t met the expectation yet.